Ethnobotanical notes about some uses of medicinal plants in Alto Tirreno Cosentino area (Calabria, Southern Italy) - Impieri Massimo; Leporatti Maria (BMC, 2007)
Abstract Background The present paper contributes to enrich the ethnobotanical knowledge of Calabria region (Southern Italy). Research was carried out in Alto Tirreno Cosentino, a small area lying between the Tyrrhenian coast and the Pollino National Park. In the area studied medicinal plants still play a small role among farmers, shepherds and other people who live far from villages and built-up areas. Methods Information was collected by interviewing native people, mainly elderly - engaged in farming and stock-raising activities - and housewives. The plants collected, indicated by the locals, have been identified according to "Flora d'Italia". The exsiccata vouchers are preserved in the authors' own herbaria. Results 52 medicinal species belonging to 35 families are listed in this article. The family, botanical and vernacular name, part of the plant used and respective manipulation are reported there and, when present, similar or identical uses in different parts of Calabria or other Italian regions are also indicated. Conclusion Labiatae, Rosaceae and Leguminosae are the families most frequently present, whilst Compositae and Brassicaceae are almost absent. The uses of the recorded species relate to minor ailments, mainly those of the skin (15 species), respiratory apparatus diseases (11), toothache, decay etc. (10) and rheumatic pains (8). The easy availability of these remedies provides a quick way of curing various minor complaints such as tooth-ache, belly and rheumatic pain and headaches and can also serve as first aid as cicatrizing, lenitive, haemostatic agents etc. The role in veterinary medicine is, on the contrary, more important: sores, ulcers, tinea, dermatitis, gangrenous wounds of cattle, and even respiratory ailments are usually cured by resort to plants.